Deskilling and upskilling with AI systems - Kevin Crowston; Francesco Bolici (Information Research: An International Electronic Journal)
Introduction. Deskilling is a long-standing prediction of the use of information technology, raised anew by the increased capabilities of AI (AI) systems. A review of studies of AI applications suggests that deskilling (or levelling of ability) is a common outcome, but systems can also require new skills, i.e., upskilling.